Application of pigtail catheter tailing combined with long-wire swapping technique in cerebral angiography via the right radial artery. Issue 39 (25th September 2020) - Yan, Dan; Zhu, Bifeng; Li, Qin; Peng, Tao; Jiang, Jingfang; Liu, Jianlin; Dan, Bitang
Abstract : Abstract: The safety and feasibility of transradial approach for cerebral angiography has been confirmed previously. However, this approach has been limited used due to the difficulty during the procedure. This study aimed to introduce a pigtail catheter tailing and long-wire swapping technique to improve the success rate without increasing complications. From August 2015 to December 2018, 560 patients who underwent cerebral angiography via transradial approach were recruited. The data including the type of aortic arch, type of Simmon catheter were collected. The loop was successfully constructed in 553 patients using Simmon-2 or Simmon-1 catheter. Of these patients, 72 patients successfully underwent cerebral and renal angiography, while 481 patients underwent cerebral angiography. The time for angiography was 52.87 ± 11.23 minutes and 47.8 ± 11.8 minutes, respectively. There were 369 (66.7%), 135 (24.4%), and 49 (8.9%) patients with type I, type II, and type III aortic arches, respectively, and their success rates of looping using Simmon-2 catheter were 97.8%, 97.0%, and 89.8%, respectively. The success rates of angiography in the right internal carotid artery, right vertebral artery, left internal carotid artery, and left vertebral artery were 100%, 100%, 98.9%, and 98.9%, respectively. No serious complications were observed in all patients. The pigtail catheter tailing and long guidewire swapping is considered as a safe procedure with high success rate for loop construction using a Simmon-2 catheter through the right radial artery, subsequently improving the success rate as well as the efficiency of angiography. Abstract : Supplemental Digital Content is available in the text